HIV-related services for men who have sex with men in Cuba in the context of COVID-19 pandemic - Betancourt Llody, Yandy Alberto; Sánchez Fuentes, Jacqueline; Molina, Niurka; Hernández Barrios, Yisel; Fuentes, Lisandra; Joanes Fiol, Jose; Baly, Alberto; Pérez Chacón, Dennis; Barrington, Clare (Revista Cubana de Medicina Tropical, 2024)
Introduction: The COVID-19 pandemic has had a major impact on the provision of HIV services to key populations. Objective: To explore the impact of COVID-19 on HIV-related services for men who have sex with men (MSM) in Cuba during the first year of the epidemic. Methods: A cross-sectional study was conducted to compare the provision of selected services between 2019 (pre-epidemic stage) and 2020 (limited autochthonous transmission, and epidemic stages). The data were extracted from two national databases in Cuba. The frequency of care by type of service was calculated on a quarterly basis in 2019 and 2020. Statistical tests were performed to determine the differences between each indicator. Results: A significant reduction in reach with the minimum HIV prevention and testing package was found in 2020 compared to 2019, especially in the second quarter of 2020 (decrease from 15.9% to 9.6% p < 0.001; and from 11.0% to 6.5% p < 0.001), which corresponds with the onset of limited autochthonous transmission, and the onset of stay-at-home and mobility limitation measures. The number of HIV-positive MSM initiating treatment (from 11.1% to 8.1%) and undergoing viral load testing during this period also decreased (from 39.9% to 36.1%). Conclusions: Reductions in the provision of HIV prevention services for MSM during the COVID-19 epidemic highlight the urgent need to adapt, innovate, and identify new opportunities for services tailored to the conditions imposed by epidemics.